Risk Analysis and Improvement of Information Systems on J&T Express Using the National Institute of Standards & Technology (NIST) 800-30 Framework - Sagita, Alda; Sandfreni, Sandfreni (Jurnal Indonesia Sosial Sains, 2025)
J&T Express is one of the leading shipping or logistics services companies in Southeast Asia. The company provides parcel delivery services with an extensive network and advanced technological infrastructure. In running its operations, J&T Express relies on complex information systems to manage the shipping process, package tracking, inventory management, and communication with customers. The reason for using the National Institute of Standards & Technology (NIST) 800-30 Framework is that this framework has been internationally recognized as a trusted standard for conducting information systems risk analysis. The NIST 800-30 Framework provides comprehensive and structured guidelines for identifying, evaluating, and managing the risks associated with the maintenance of information systems. By implementing this Framework, J&T Express can adopt a structured and standardized approach to conducting risk analysis, allowing it to identify potential threats, analyze their impacts, and take appropriate precautions. The results of this study aim to provide a comprehensive analysis of maintenance risks in the J&T Express information system. The study will identify potential risks and vulnerabilities and propose strategies to mitigate them. In addition, this research will contribute to improving the overall safety and reliability of J&T Express' information systems, ensuring that its operations run smoothly and data integrity is maintained.